"One family, two systems": Food safety crisis as a catalyst for agrarian changes in rural China. (July 2019) - Si, Zhenzhong; Li, Yanyan; Fang, Ping; Zhou, Li
Abstract: The political economy of agrarian changes in rural China has attracted much scholarly attention. Yet these studies have placed limited emphasis on the role of food safety crisis, a critical issue that not only motivated consumption changes of urban residents, but also catalyzed a differentiated food production and supply scheme in rural China. Our extensive fieldwork revealed that more than 60% of rural farming households in China are adopting two distinctive farming approaches: conventional production with intensive usage of agrochemicals for selling to the market and ecological production with limited or no usage of agrochemicals for self-consumption, relatives and people with close social ties. This is what we call 'one family, two systems'. This paper conceptualizes and illustrates the widespread yet rarely discussed phenomenon with specific cases. We argue that 'one family, two systems' is farmers' self-protection response to the heightened food safety crisis. It reveals that the access to ecologically produced food in the common phenomenon is determined by farmers' social relations and thus is embedded in local social network. 'One family, two systems' fosters agrarian changes in at least two dimensions – the farmer-driven ecologicalization of food production and the re-embedding of food production and consumption in ecological systems and social relations in rural China. Highlights: 'One family, two systems' depicts the common differentiated food practices in China. The food safety crisis catalyzes the proliferation of 'one family, two systems'. 'One family two systems' is a self-protection mechanism of farming households. Farmers' social circles are defined by their obligation and affection with others. Access to quality food is determined by one's position in farmers' social circles.